ДИДАКТИЧНІ УМОВИ ЕФЕКТИВНОЇ ПОБУДОВИ ІНФОРМАЦІЙНО-ОСВІТНЬОГО СЕРЕДОВИЩА ВИШУ (Pedagogy of Higher and Secondary Education, 2012)
У статті обґрунтовано дидактичні умови ефективної побудови інформаційно-освітнього середовища вишу.Ключові слова: дидактичні умови, інформаційно-освітнє середовище.The didactic conditions of effective constructions of the information-educational environment of a higher educational institution are substantiated in the article.Key words: didactic conditions, the information-educational environment of a higher educational institution.
Keywords: didactic conditions; the information-educational environment of a higher educational institution